Factors influencing the self-perceived mobility of active unilateral lower limb amputees assessed with the Prosthetic Mobility Questionnaire: a brief report. Issue 1 (26th December 2022) - Morosato, Federico; Gentile, Cosimo; Di Bernardo, Arianna; Gruppioni, Emanuele; Miccio, Antonella
Abstract : The Prosthetic Mobility Questionnaire (PMQ 2.0) represents a reliable solution for evaluating amputees' self-perceived mobility. The study aimed to evaluate the perceived mobility of middle-aged users with a traumatic amputation using the PMQ 2.0 and to assess the influence of age, stump and phantom limb pain, amputation level, time since amputation, and prosthesis use on it. Fifty subjects were recruited. The median value of the score was higher than previously published reference values, reflecting the 'active' mobility status of the sample. The hours of prosthesis use per day explained about 21% of the variance of the questionnaire score and was a significant predictor of perceived mobility. Reference values for the recently developed PMQ 2.0 survey and relative to active, traumatic amputees were reported. As prosthesis use was a significant predictor of the amputees' perceived mobility, prolonged use of the artificial limb should be always encouraged in clinical practice.